Actinic Keratoses: A Comprehensive Update - Ibrahim, Sherrif F. (Matrix Medical Communications, 2009)
Actinic keratoses are common intra-epidermal neoplasms that lie on a continuum with squamous cell carcinoma. Tightly linked to ultraviolet irradiation, they occur in areas of chronic sun exposure, and early treatment of these lesions may prevent their progression to invasive disease. A large variety of effective treatment modalities exist, and the optimal therapeutic choice is dependent on a variety of patient- and physician-associated variables. Many established and more recent approaches are discussed in this review with a focus on efficacy and administration techniques. Several previously experimental options, such as imiquimod and photodynamic therapy, have become incorporated as first-line options for the treatment of actinic keratoses, while combination treatment strategies have been gaining in popularity. The goal of all therapies is to ultimately limit the morbidity and mortality of squamous cell carcinoma. (J Clin Aesthetic Dermatol. 2009;2(7):43–48.)